Antibody responses to equine parapoxvirus reveal a re-emerging pattern - Pettersson, Jenni; Levanov, Lev; Tervo, Sanna; Hautala, Katja; Aaltonen, Kirsi; Utriainen, Mira; Kareinen, Lauri; Gadd, Tuija; Sironen, Tarja; Vapalahti, Olli; Kinnunen, Paula M. (Springer Nature, 2026)
Background
Parapoxviruses (PPV) cause skin and mucous membrane signs to several animal species and humans worldwide. Equine parapoxvirus (EqPPV) was first detected in a sick horse in Finland in 2013. It is potentially zoonotic, and a similar virus has been detected in humans in the USA. In winter 2021–2022, EqPPV caused a large-scale pastern dermatitis epidemic in racehorses all over Finland. Field reports suggest that similar epidemics of unverified cause have also occurred in 2015 and 2019. The aim of this study was to develop a serological test and study the immune response, seroprevalence, and history of the virus utilizing serum samples from clinical cases and archived horse samples (2012–2022).
Results
A recombinant protein-based immunofluorescent assay was established using envelope proteins B2L and F1L. EqPPV induced a fast immune response within a few days from the onset of the clinical signs. Two horses that were additionally tested a year after the disease still had similar IgG titers as a year prior. Seroprevalence peaks coincided with reported outbreaks in 2015 and 2022 (yearly variation: 1.8–14.6% [B2L] and 3.6–16.7% [F1L]).
Conclusions
The results suggest that EqPPV is a re-emerging pathogen that has a potential to cause large epidemics, bringing a need for more studies and preparedness.